The Effect of Environmental, Social and Governance (ESG) on Stock Returns with Company Size as a Moderating Variable - Octaviani, Rr. Annisa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The capital market encompasses actions like public offerings and trading in securities, listed companies, and the securities they produce, along with professional organizations that participate in securities operations, in line with the guidelines outlined in Capital Market Law No. 8 of 1995. This study investigates how Environmental, Social, and Governance (ESG) factors influence stock returns in manufacturing firms, considering company size as a moderating factor, listed on the IDX from 2022 to 2024. This research is quantitative in nature. The group being studied includes every manufacturing firm that is registered on the IDX from 2022 to 2024. The sample for this research comprises all 673 manufacturing firms. The analysis of data in this study involves descriptive evaluation of research data, descriptive statistics, correlation matrices, Data analysis involved Moderated Regression Analysis (MRA), complemented by hypothesis testing using t-tests, F-tests, and R² evaluation. The findings indicate that (1) the negative relationship of ESG cannot partially affect stock returns, but with the presence of control variables, it can simultaneously affect stock returns, (2) the negative relationship between ESG and company size cannot partially affect stock returns. However, with the presence of control variables and moderation from company size, ESG can simultaneously affect stock returns.